2022
DOI: 10.1021/acs.langmuir.2c01721
|View full text |Cite
|
Sign up to set email alerts
|

Textural Characterization by Using an Alternative Langmuir Isotherm and a New Thickness Function

Abstract: Samples with micropores can not be adequately described by using the Langmuir isotherm. The Langmuir expression is obtained by using the monolayer assumption, which is not valid in samples with micropores. Then, we propose to include in the isotherm a corrective parameter related to the sample porosity. We show that the modified isotherm enables us to describe the experimental values for different samples (aluminas, clays, silicas, zeolites, and zirconias) in low and full relative pressure ranges. Indeed, a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The specific surface area is a crucial textural characteristic of the samples, and it is usually determined using the BET isotherm to describe the experimental data of nitrogen sorption. However, by Ref Mojica et al Mojica-Sepúlveda et al (2022) showed that the BET isotherm underestimates the value of the specific surface area of the samples. In this work, an alternative isotherm is proposed that provides an accurate description of nitrogen sorption in the samples.…”
Section: Textural Characterization Using Sorption Of Nitrogenmentioning
confidence: 98%
“…The specific surface area is a crucial textural characteristic of the samples, and it is usually determined using the BET isotherm to describe the experimental data of nitrogen sorption. However, by Ref Mojica et al Mojica-Sepúlveda et al (2022) showed that the BET isotherm underestimates the value of the specific surface area of the samples. In this work, an alternative isotherm is proposed that provides an accurate description of nitrogen sorption in the samples.…”
Section: Textural Characterization Using Sorption Of Nitrogenmentioning
confidence: 98%